Comparative efficacy of some current diagnostic techniques for diagnosis of chlamydiosis among domestic poultry and wild carriers - CHAHOTA, RAJESH; KATOCH, R C (The Indian Journal of Animal Sciences, 2013)
Samples, 186, from visceral organs (lung, liver, heart and spleen) and 130 faecal swabs/intestinal contents, accruing from chickens (181), pigeons (55), parrots (19), crows (11), house sporrows (6), doves (4), nightingales (2), Indian myanas (2), wall lizards (10), frogs (14) and rats(12) were screend for Chalamydia psittaci by using techniques, viz. isolation using embryonated chicken eggs, and indirect microimmunofluorescent test (IMIFT) and Wolbach's Giemsa staining on direct impression smears of all samples. Irrespective of species, 39 (12.34%) cases were positive by isolation studies, 55 (17.40%) by IMIFT and 30 (9.49%) by Wolbach's Giemsa staining method. The IMIFT was the most sensitive test for screening chickens and wild fauna for chlamydiosis, chlamydiosis, especically for quick preliminary screening of large samples.